A new Adamts9 conditional mouse allele identifies its non‐redundant role in interdigital web regression. Issue 7 (8th May 2014) - Dubail, Johanne; Aramaki‐Hattori, Noriko; Bader, Hannah L.; Nelson, Courtney M.; Katebi, Negin; Matuska, Brittany; Olsen, Bjorn R.; Apte, Suneel S.
Summary ADAMTS9 is the most conserved member of a large family of secreted metalloproteases having diverse functions. Adamts9 null mice die before gastrulation, precluding investigations of its roles later in embryogenesis, in adult mice or disease models. We therefore generated a floxed Adamts9 allele to bypass embryonic lethality. In this mutant, unidirectional loxP sites flank exons 5–8, which encode the catalytic domain, including the protease active site. Mice homozygous for the floxed allele were viable, lacked an overt phenotype, and were fertile. Conversely, mice homozygous for a germ‐line deletion produced from the floxed allele by Cre‐lox recombination did not survive past gastrulation. Hemizygosity of the deleted Adamts9 in combination with mutant Adamts20 led to cleft palate and severe white spotting as previously described. Previously, Adamts9 haploinsufficiency combined with either Adamts20 or Adamts5 nullizygosity suggested a cooperative role in interdigital web regression, but the outcome of deletion of Adamts9 alone remained unknown. Here, Adamts9 was conditionally deleted in limb mesoderm using Prx1‐Cre mice. Unlike other ADAMTS single knockouts, limb‐specific Adamts9 deletion resulted in soft‐tissue syndactyly (STS) with 100% penetrance and concurrent deletion of Adamts5 increased the severity of STS. Thus, Adamts9 has both non‐redundant and cooperative roles in ensuring interdigital web regression. This new allele will be useful for investigating other biological functions of ADAMTS9. genesis 52:702–712, 2014. © 2014 Wiley Periodicals, Inc.